Structural and optical properties of ZnO thin films deposited using atomic layer deposition technique - PPKBSM, Pusat Pengajian Bahan & Sumber Mineral (2011)
ZnO films have been successfully deposited by Atomic Layer Deposition (ALD) using Diethylzinc (DEZn) and water (H2O) as precursors.